Fluorescence lifetime activated droplet sorting (FLADS) for label-free sorting of Synechocystis sp. PCC6803. Issue 8 (25th March 2022) - Blaha, Maximilian Emanuel; Hasan, Sadat; Dusny, Christian; Belder, Detlev
Abstract : This study presents the label-free sorting of cyanobacterial cells in droplets with single-cell sensitivity based on their fluorescence lifetime. Abstract : This study presents the label-free sorting of cyanobacterial cells in droplets with single-cell sensitivity based on their fluorescence lifetime. We separated living and dead cyanobacteria ( Synechocystis sp. PCC6803) using fluorescence lifetime signals of the photopigment autofluorescence to indicate their photosynthetic activity. We developed a setup and a chip design to achieve live/dead sorting accuracies of more than 97% at a droplet frequency of 100 Hz with a PDMS-based chip system and standard optics using fluorescence lifetime as the sorting criterion. The obtained sorting accuracies could be experimentally confirmed by cell plating and observing the droplet sorting process via a high-speed camera. The herein presented results demonstrate the capabilities of the developed system for studying the effects of stressors on cyanobacterial physiology and the subsequent deterministic sorting of different stress-response phenotypes. This technology eliminates the need for tedious staining of cyanobacterial cells, which makes it particularly attractive for its application in the field of phototrophic microbial bio(techno)logic and in the context of cell secretion studies.